Slilica, Hyaluronate, and Alveolar Macrophage Functional Differentiation. (1st March 2003) - Bodo, Maria; Bellocchio, Silvia; Bellucci, Catia; Balloni, Stefania; Pietrella, Donatella; Sbaraglia, Giovanni; Muzi, Giacomo; Lilli, Cinzia; Lumare, Alessandro; Dell'Omo, Marco; Abbritti, Giuseppe
Abstract : Background: Silicosis is mediated by macrophages, their soluble mediators, and extracellular matrix molecules. In this study, we investigated the effects of silica and/or hyaluronate (HA) on several alveolar macrophage responses. Methods: We evaluated glycosaminoglycan (GAG) production by radiolabeled precursors, nitric oxide (NO) release by its oxidation product, phagocytic activity by Candida albicans internalization, and the secretion of two fibrogenic cytokines, tumor necrosis factor (TNF)-α and transforming growth factor (TGF)-β, by specific assays. Results: Silica significantly reduced GAG secretion, particularly HA secretion. Alone, it decreased Candida uptake; associated with HA, it enhanced the reduction. Silica and Candida reduced NO release, which was not significantly affected when silica- or Candida -exposed cells were also treated with HA. TNF-α and TGF-β activities were stimulated by silica but reduced by HA. Conclusions: The results suggest that silica and HA modify alveolar macrophage functional differentiation. Silica- and HA-induced modifications of the microenvironment could determine whether the response proceeds toward healing and repair or toward lung chronic pathology.